2010
DOI: 10.1007/s10545-010-9210-7
|View full text |Cite
|
Sign up to set email alerts
|

The 3‐methylglutaconic acidurias: what's new?

Abstract: The heterogeneous group of 3-methylglutaconic aciduria (3-MGA-uria) syndromes includes several inborn errors of metabolism biochemically characterized by increased urinary excretion of 3-methylglutaconic acid. Five distinct types have been recognized: 3-methylglutaconic aciduria type I is an inborn error of leucine catabolism; the additional four types all affect mitochondrial function through different pathomechanisms. We provide an overview of the expanding clinical spectrum of the 3-MGA-uria types and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 77 publications
2
68
0
6
Order By: Relevance
“…There is a rapidly growing group of IEMs with a syndromic phenotype reviewed by Wortmann, Kluijtmans, Engelke, Wevers, and Morava (2012) and Wortmann et al (2013) causing secondary 3‐methylglutaconic aciduria (3‐MGA) due to defective phospholipid remodeling or mitochondrial membrane associated disorders. The excretion of 3‐MGC can be highly variable or intermittently normal in secondary 3‐MGA and is generally less than levels seen in primary 3‐MGA due to AUH .…”
Section: Discussionmentioning
confidence: 99%
“…There is a rapidly growing group of IEMs with a syndromic phenotype reviewed by Wortmann, Kluijtmans, Engelke, Wevers, and Morava (2012) and Wortmann et al (2013) causing secondary 3‐methylglutaconic aciduria (3‐MGA) due to defective phospholipid remodeling or mitochondrial membrane associated disorders. The excretion of 3‐MGC can be highly variable or intermittently normal in secondary 3‐MGA and is generally less than levels seen in primary 3‐MGA due to AUH .…”
Section: Discussionmentioning
confidence: 99%
“…AUH = 3-methylglutaconyl-CoA hydra-tase (enzyme deficient in 3-MGAuria type I). HMG-CoA = 3-hydroxy-3-methylglutaryl CoA (adapted from (Wortmann et al 2010a)) these patients 30 % are reported with 3-MGA-uria (Gibson et al 1992;Jakobs et al 1991;Knerr et al 2003;Krauch et al 2002;Lichter-Konecki et al 1993). Curiously, mitochondrial deletions presenting with the Kearns-Sayre phenotype do not lead to 3-MGA-uria.…”
Section: Correlation Of 3-mga-uria With Specific Mitochondrial Disordersmentioning
confidence: 99%
“…Another indication of a possible HuChrX-link in MCC deficiency was the report wherein six of eight patients who presented with metabolites of MCC deficiency, but for whom no MCC mutations could be detected were males [17]. The incidence of 3-methylglutaconic aciduria Type-I, another autosomal recessive disorder of the leucine catabolism, also seems to be higher in males than in females [16,102]. The apparent HuChrX link in both MCC and MCGAType-I deficiencies could be coincidental, but should be further investigated.…”
Section: Discussionmentioning
confidence: 99%